The Distribution of PSA Age-Specific Profiles in Healthy Irish Men between 20 and 70. (8th July 2012) - Casey, R. G.; Hegarty, P. K.; Conroy, R.; Rea, D.; Butler, M. R.; Grainger, R.; McDermott, Ted; Thornhill, J. A
Abstract : Background . Ireland is estimated to have the highest European incidence rate of prostate cancer (Pca) in 2006 which will increase by 275% by 2025. This study aimed to determine PSA cutoff values in different age groups of healthy male patients without Pca. Methods . 660 men in a pilot men's health programme, aged 18–67, had PSA assayed. Men were grouped into 8 age groups at 5-year intervals: 30–34, 35–39, 40–44, 45–49, 50–54, 55–59, 60–64, and 64–70. Results . Linear regression demonstrates a PSA velocity of 0.024 ng/ml/year. The 95% confidence interval demonstrates a near flat line of PSA values from age 20 to 50 and rises after. When transformed logarithmically, PSA correlates highly with expected values from the normal distribution (0.98). A fractional polynomial quantile regression model was used to predict median and 95th percentile for PSA as follows: 30–34 (0.73, 1.57), 35–39 (0.71, 1.65), 40–44 (0.73, 1.85), 45–49 (0.78, 2.17), 50–54 (0.88, 2.63), 55–59 (1.01, 3.25), 60–64 (1.20, 4.02), and 64–70 (1.43, 4.96). Conclusions . PSA levels are similar to other racial groups but not as high as US Caucasians until 65 years. These data define the predicted PSA for the Irish population and provide a reference for future screening programmes.